COVID-19 in India: Health implications and treatment needs of people who use drugs (PWUD) and patients with substance use disorders (SUD) - Gautam Kr GHOSH (Journal of Health and Social Sciences)
Introduction: The COVID-19 induced lockdown in India had put large number of people who use drugs (PWUD) in panicky over their craving for substance use with supply chain disruptions. Aim of this paper was to understand the COVID-19 induced problems faced by PWUD and those with substance use disor- ders (SUD) in India. Methods: A rapid qualitative research was conducted remotely from May to early June 2020, during lock- down period in India, with consent-based in-depth interviews with key stakeholders from national agencies and drug deaddiction center in East and Northern-East India. Results: The current public health crisis raises serious additional concerns for the wellbeing of PWUD as they run the same risks of infection by COVID-19 due to underlying chronic medical conditions. During the current COVID-19 pandemic, there has been persistent lacking of treatment services for patients with substance use disorders (SUD). Those who needed treatment during lockdowns faced problems as govern- ment supported drug deaddiction centers, which stopped new admission but lately started new admission but in reduced numbers. The outpatient services of drug treatment centers (DTC) at some government ho- spitals could not operate. The Opioid Substitution Therapy centers, though started dispensing of methadone on biweekly and buprenorphine on seven-day refill basis, yet there remained travel related problems and reported harassment during lockdown stage. Conclusion: Specific measures to mitigating health service needs of PWUD in India should be put in place, taking lessons from the current pandemic situation.